Exploring the use of smartphone applications during navigation-based tasks for individuals who are blind or who have low vision: future directions and priorities. - Bleau, Maxime; Martiniello, Natalina; Gingras-Royer, Nathalie; Tardif-Bernier, Catherine; Nemargut, Joseph Paul (Disability & Rehabilitation: Assistive Technology, 2026)
Purpose: Mainstream smartphone applications are increasingly replacing the use of traditional visual aids to facilitate independent travel for people with blindness or low vision. However, little is known about which navigation apps are being used, the factors underpinning these decisions and why apps are not used in certain contexts. The goal of this study was to explore the navigation-based apps used by individuals who are blind or who have low vision, the factors influencing these decisions, and perceptions about gaps to address future needs in navigation. Materials and Methods: An international online survey was conducted with 139 participants who self-identified as blind or low vision. Results: Findings indicate that the decision to use an app based on artificial intelligence (AI) versus live video assistance is related to whether the task is dynamic or static in nature. Although most participants rely on apps only during unfamiliar routes (60.9%), apps are shown to supplement rather than replace traditional tools such as the white cane and dog guide. Participants underscore the need for future apps to better assist with indoor navigation and to provide more precise information about points of interest (POI). Conclusion: These results provide vital insights for technology developers about the perceived utility of smartphone apps for people with low vision or blindness during navigation. Our results highlight the importance of built-in accessibility features for users with visual impairments. As additional technology-based solutions are developed, it is essential that blind and low vision users, including rehabilitation professionals, are meaningfully included within design. IMPLICATION FOR REHABILITATION: Navigation applications supplement, rather than replace traditional rehabilitation strategies and tools, such as the white cane and guide dog. Rehabilitation practitioners can support clients in learning how and when to draw on these tools alongside primary orientation and mobility strategies. Mainstream navigation applications are not consistently accessible to people with visual impairments who bring different levels of technology competency and do not respond to their needs for indoor navigation. Rehabilitation practitioners should review the accessibility and usability of these applications prior to use within intervention, and work alongside individuals with visual impairments to advocate for proactive accessibility. Applications using AI-based computer vision are perceived by participants to be most helpful for visual identification of objects, while GPS-based applications are useful for planning routes, using public transportation, and finding points of interest (POI). Often, no applications were used for street crossings or obstacle detection tasks. Based on this knowledge, rehabilitation practitioners can introduce the advantages and limitations of different solutions to clients who are new to using these applications as part of the training process. The most common reasons for not using a navigation-based application were that none were known, they were not needed in familiar environments, or traditional orientation and mobility skills were sufficient. This highlights the value and importance of technological developments to address persisting client barriers, while also recognising that technology is not the only or best solution for all contexts.